The Implementation of E-Module Based on Problem-Based Learning To Improve The Analytical Thinking Ablities and Reduce Misconception of X MIA 1 Of SMA Negeri 1 Banyudono Academic Year of 2014/2015 - Muhammad Furqan; Puguh Karyanto; Yudi Rinanto; Sitti Salma (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
The objectives of this research were to improve the ability of critical thinking and reduce misconception of X-MIA 1 SMA Negeri Banyudono academic year of 2014/2015 through the implementation of e-module based on Problem-Based Learning. This research was a class action research conducted in two cycles. Every cycle consists of 4 stages, namely: planning, action, observing, and reflecting. The data of this research was obtained from observation and test. This research was descriptive qualitative. There were three analysis components: data reduction, data presentation, and taking the conclusion. Data validation of this research was triangulation method. This research used spiral model that adopted from Kemmis and Mc Taggart respectively. The results of this research showed an improvement of analytical thinking ability, they were 32% in indentifying an important aspect, 32% in figuring the series of process, 29% in the aspect data analysis, and 31% in the aspect of interpretation. On the other side, the results of this research showed the decreasing of student’s misconceptions, they were 39% in attribute concept of population, 40% in attribute concept in community, 31% in the concept of food chain and web, and 26% in the ecology concept in science, environment, technology and community (salingtemas). The conclusion of this research was the implemetation of e-module based on Problem-Based Learning was able to improve the ability of critical thinking and reduce misconception of X of MIA 1 SMA Negeri 1 Banyudono in academic year of 2014/2015.Keywords: E-module based on Problem-Based Learning, analytical thinking, misconception